2014
DOI: 10.1007/s11060-014-1381-x
|View full text |Cite
|
Sign up to set email alerts
|

Intensive chemotherapy followed by reduced-dose radiotherapy for biopsy-proven CNS germinoma with elevated beta-human chorionic gonadotropin

Abstract: In this study, 10 patients with biopsy-proven germinoma with a beta-human chorionic gonadotropin (β-HCG) level >50 mIU/ml received intensive chemotherapy followed by reduced-dose radiotherapy (RT) to reduce late effects from RT. CSF β-HCG levels were >200 mIU/ml in five patients. After endoscopic or stereotactic biopsy, four cycles of induction chemotherapy were administered prior to RT. A CEB regimen (carboplatin + etoposide + bleomycin) and a CyEB regimen (cyclophosphamide + etoposide + bleomycin) were alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, considering the similar incidence of relapse identified outside the CSF circulation route, incomplete CSF information could not fully explain the unique relapse pattern in patients with BG germinoma. Moreover, the sensitivity of CSF cytology varies significantly across institutes, with positivity rates as high as 52% in early reports and as low as 1.1% in studies with LGG [24] (n = 195) **p value Healthy population [24] (n = 205) **p value NHL/CLL [24] (n = 100) **p value GCTs [23] ( larger sample sizes [3,[30][31][32]. Based on our limited data, one of the seven patients with metastasis excluded from the current study tested positive by CSF cytology, while six were positive on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the similar incidence of relapse identified outside the CSF circulation route, incomplete CSF information could not fully explain the unique relapse pattern in patients with BG germinoma. Moreover, the sensitivity of CSF cytology varies significantly across institutes, with positivity rates as high as 52% in early reports and as low as 1.1% in studies with LGG [24] (n = 195) **p value Healthy population [24] (n = 205) **p value NHL/CLL [24] (n = 100) **p value GCTs [23] ( larger sample sizes [3,[30][31][32]. Based on our limited data, one of the seven patients with metastasis excluded from the current study tested positive by CSF cytology, while six were positive on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, RT > 2,340 cGy was a risk factor for SMN development, whereas no difference was observed in the development of SMN in patients who received RT ≤ 2,340 cGy compared to those who did not receive RT. Our center has adopted a strategy to reduce the RT dose to decrease late sequelae in pediatric cancer survivors, especially those with brain tumors, including intracranial germ cell tumors and medulloblastomas [ 7 , 28 , 29 ]. As RT is an important modality in the treatment of pediatric cancer, its use is inevitable; however, reducing the radiation dose whenever possible is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy with cyclophosphamide, ifosfamide, etoposide, cisplatin, and carboplatin were highly effective in CNS GCTs. 24 However, chemotherapy alone was proven to be inferior compared to radiotherapy-based treatment protocols. The Second International CNS Germ Cell Study Group showed that intensive chemotherapy was effective only in one-third of patients with 5-year event free survival and overall survival rates were 36% and 75%, respectively, and patients were salvaged through radiotherapy.…”
Section: Discussionmentioning
confidence: 99%